Digitalized Polarization Fading Suppression and Phase Demodulation Scheme of Phase-Sensitive Optical Time-Domain Reflectometry Based on Polarization Diversity Virtual Coherence - Xiatong Wu; An Sun; Yanming Liu; Wei Ji (Photonics)
In this paper, a digitalized polarization fading suppression and phase demodulation technique for a phase-sensitive optical time-domain reflectometry (φ-OTDR) sensing system utilizing polarization diversity virtual coherence is proposed, in which virtual cross-coherence between the polarization diversity digital signals is employed for simultaneous fading noise suppression and phase demodulation. The principle of the proposed demodulation algorithm is presented and analyzed. Based on this, the practicability and validity of the proposed demodulation method for fading noise suppression and distributed vibration sensing are confirmed through experiments. The experimental results indicate that the proposed demodulation scheme can effectively reduce the polarization fading noise caused by the polarization mismatch between the probe light and the reference light, and the phase changes induced by external interference can also be accurately recovered with a signal-to-noise ratio (SNR) of vibration signal localization of 27.14 dB and an SNR of vibration signal phase demodulation of 47.88 dB, which provides a simplified method for simultaneous polarization fading suppression and the phase demodulation of the φ-OTDR system.